ANALYSIS BALANCED SCORECARD IN NON-PROFIT ORGANIZATIONS TO ACCOUNTABILITY IN THE COVID PANDEMIC - Mufidah Mufidah; Amri Amir; Achmad Hizazi; Enggar Diah Puspa Arum (Dinasti Publisher, 2022)
This study examined the impact of internal control on non-profit organization performance and impact of internal control on accountability both directly and indirectly with pandemic covid as one of environmental uncertainties as a moderation variable. As a result, environmental uncertainty was examined as a moderator variable. This study analyzed 90 observations using cross-section data and primary data sources.. Internal control have an effect on organizational performance and accountability while environmental uncertainty has no effect as a moderating variable.